In-vitro and in-vivo evaluation of therapeutic properties of skin mucus from asian swamp eel (monopterus albus) - Hilles, Ayah Rebhi Mohammad
Swamp eels have been widely accepted as sources of food, especially among various Asian cultures. However, their potential values as novel sources of therapeutic agents have not been widely appreciated. Like most other tropical fishes and amphibians, the outer integumentary system of Monopterus albus is covered with mucus layers, which may act as mechanical and biochemical barrier for their skin. The biochemical components of these mucus layers may have certain compounds that may be medically beneficial to human. The current study was interested to screen selected biological activities of skin mucus from the tropical eel in-vitro and in-vivo. The first stage of the study was the screening of the eel skin mucus extracts for bioactive compounds using gas chromatography-mass spectrometry and liquid chromatography quadrupole-time-of-flight mass spectrometry. Several compounds, which had been previously identified to have different biological activities mainly cytotoxic, antioxidant and antimicrobial activities were discovered. The second stage of the study aimed to demonstrate and investigate the anti-oxidative, anti-cancer and antimicrobial activities in-vitro models. The antioxidant results revealed that methanolic extract showed higher activity than aqueous extract with higher phenolic and flavonoid contents as well as higher antioxidant assays which including DPPH radical scavenging and β-carotene bleaching. Preliminary cytotoxicity study was demonstrated against human lung carcinoma cell line (A549) using cell viability assay which revealed that methanolic extract is more potent than aqueous extract as IC50 values were 621±0.09 μg/mL and 845 ± 0.25 μg/mL respectively. It was then established that the methanolic extract was able to induce apoptosis in A549 cell line by the activation of caspase-3, 8 and 9. Further analyses to investigate the mode of cell death induction and cell cycle arrest pathways by flow cytometry analysis revealed that the methanolic extract was able to induce late apoptosis and arrested the cells in G0/G1 phase. Assessment of antimicrobial activities of the eel mucus extracts against several bacterial and fungal strains was conducted using diffusion method. Methanolic extract at 100 μL/well was found to inhibit the growth of Microsporum gypseum and Aspergillus niger. Significantly. Furthermore, the methanolic extract at 100 μL/disc significantly inhibited the growth of Staphylococcus aureus and Escherichia coli. Comprehensive evaluation of antimicrobial activities against selected oral pathogens showed that methanolic extract exhibited high activity against Enterococcus faecalis, Streptococcus mutans, Streptococcus pyogenes, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Candida albicans. For in-vivo study, a topical gel delivery system used from eel skin mucus formulated gel to apply into the infected rat skins. Sprague Dawley rats were divided into normal, positive control, negative control, and treated groups. The infections were introduced to the rats by intracutaneous injections of pathogenic bacteria and fungi. The development of impetigo, tinea capitis and cutaneous candidiasis in the animal model was confirmed based on the clinical and histological observations. Following that, the infected rats were treated topically with the formulated gel from eel mucus extract. The histological analysis of the skin tissues which treated with the formulated gel was shown a complete recovery in the skin tissues at a similar rate as the control antibiotic groups. In conclusion, the present study revealed that eel skin mucus formulated gel efficient therapeutic candidate in treating skin infections which can be considered as a novel discovery as a natural alternative treatment for certain skin diseases.